2021
DOI: 10.3171/2020.6.spine20318
|View full text |Cite
|
Sign up to set email alerts
|

Odontoid screw placement for Anderson type II odontoid fractures: how do duration from injury to surgery and clinical and radiological factors influence the union rate? A multicenter retrospective study

Abstract: OBJECTIVEAnderson type II odontoid fractures are severe conditions, mostly affecting elderly people (≥ 70 years old). Surgery can be performed as a primary treatment or in cases of failed conservative management. This study aimed to investigate how duration from injury to surgery, as well as clinical, radiological, and surgical risk factors, may influence the union rate after anterior odontoid screw placement for Anderson type II odontoid fractures.METHODSThe authors conducted a retrospective multicenter study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“… 27 , 28 , 29 , 30 In the last few decades, Minimally Invasive Surgery (MIS) has been proposed as an alternative to conventional surgery for many different conditions affecting the spine. 27 , 31 , 29 , 30 , 32 MIS has been found to preserve the anatomical and functional integrity of spine muscles and peri-articular tendons, as well as reduce intra-operative blood loss, post-operative pain, and hospitalization time. 8 , 33 , 34 , 27 , 35 Although MIS has been shown to improve quality of life and pain, 36 , 37 its effects on gait behavior have only been investigated in terms of spatiotemporal and kinetic parameters of the lower limbs, with less compensation between lower limbs reported after surgery.…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 28 , 29 , 30 In the last few decades, Minimally Invasive Surgery (MIS) has been proposed as an alternative to conventional surgery for many different conditions affecting the spine. 27 , 31 , 29 , 30 , 32 MIS has been found to preserve the anatomical and functional integrity of spine muscles and peri-articular tendons, as well as reduce intra-operative blood loss, post-operative pain, and hospitalization time. 8 , 33 , 34 , 27 , 35 Although MIS has been shown to improve quality of life and pain, 36 , 37 its effects on gait behavior have only been investigated in terms of spatiotemporal and kinetic parameters of the lower limbs, with less compensation between lower limbs reported after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Because individuals with osteoporosis demonstrate slower and less reliable bony healing, AOSF in these individuals may contribute to nonunion, revision surgery, and mortality. Ricciardi et al 35 demonstrated that osteoporosis (OR: 4.0) and diabetes (OR: 3.35) were both independently associated with nonunion. In addition, complications such as dysphagia and pneumonia must be specifically considered in this population.…”
Section: Anterior Fixationmentioning
confidence: 99%
“…Early surgery should be indicated if medically stable because delayed surgical intervention more than 1 week after presentation confers 48 times greater odds of nonunion. 35 When surgical intervention is selected, elderly patients should generally undergo a posterior approach. While an anterior approach is possible, we believe this should only be considered by experienced surgeons and favorable radiographic fracture patterns because the benefits of preserved intersegmental motion may not be worth the risks associated with implant failure.…”
Section: Author Recommendationsmentioning
confidence: 99%
“…They report mostly positive outcomes, with satisfactory union rates ranging around 75%-96% and few complications. [13][14][15][16][17] However, these studies have generally been small series and may be subject to bias. Due to publication bias, case reports and case series which are published predominantly report on successful interventions rather than treatment failures.…”
mentioning
confidence: 99%
“…Since 1990, there have been numerous reports of its use in acute dens fractures. They report mostly positive outcomes, with satisfactory union rates ranging around 75%–96% and few complications 13–17 . However, these studies have generally been small series and may be subject to bias.…”
mentioning
confidence: 99%